China: Shadow WTO agricultural domestic support notifications - Cheng, Fuzhi (International Food Policy Research Institute, 2008)
This paper reviews recent agricultural policy changes in China and presents estimates of domestic support for the period 1996-2005. A set of relevant alternative subsidy-definition scenarios and their effects on the calculated levels of support are analyzed, and a projection of domestic support through 2013 is presented. The paper concludes with a discussion of new WTO rules that may be negotiated in the Doha Round and their implications for China. Based on standard WTO subsidy calculation methods, our results indicated that China's domestic support for the period 1996-2005 has been well below the limits agreed at its WTO accession. The market price support (MPS) component of the aggregate measure of support (AMS) in China has been below zero, and this has dwarfed the relatively small but positive non-product specific AMS and led to a zero current total AMS after de minimis. China has no AMS commitments but can provide trade-distorting domestic support to agricultural producers up to 8.5 percent of the value of production (or RMB561 billion). Thus there appears to be substantial room for China to extend its amber box subsidy measures through heavy use of the de minimis provision. We project domestic support notifications through 2013 based on specified assumptions about domestic policies, including changes in administered prices and commodity program coverage. New rules potentially negotiated in the Doha Round are expected to provide more constraints on subsidies. Due to China's developing country status, with no AMS commitments under the Uruguay Round Agreement on Agriculture the impacts of these new constraints are shown to be limited, although our projections indicate that China may exceed its WTO commitment levels under certain price and commodity coverage scenarios.